Groups of deviations of Fourier series in generalized Hölder spaces - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We study the rate of convergence of the values of analogs of the functionals of strong approximation of Fourier series ingeneralized $L$-Hölder spaces.